Optimasi Produksi Usaha Ayam Goreng Tepung Menggunakan Metode Simpleks - Shelvyana Marcgaret Pujianto; Nidia Rosmawanti (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2015)
Any attempt at anything like to get optimal benefits in production. Therefore we need a tool that is able to help solve the problem in order to obtain optimal benefits based on available resources.Simplex method is used to determine the exact amount of production at a cottage industry producing flour fried chicken in order to get optimal benefits. During this time, the cottage industry estimates only just the amount of production per day, so it is often quite a lot left over residue production, because it is to help simplify the process of constructing calculation application "Chicken Fried Flour Optimization Using Linear Programming Simplex Method" using the software Borland Delphi 7 and MySQL database.After passing the test data with the raw material to produce flour fried chicken along with the time available capacity using the simplex method, it can be seen that the benefits increase compared to before using simpeks. Keywords: Optimization of production, maximizing profits, Linear Programming, Simplex method